FORMATION OF SCENARIOS TO ENSURE TERRITORIAL DEVELOPMENT OF LAND USE OF REGIONS - Mamonov, К.; Kovalchuk, V.; Tkachuk, V.; Kovalev, D. (Municipal economy of cities. Series: «Economy science», 2025)
To solve urgent problematic issues regarding land use, it is proposed to apply methods and models of mathematical modeling and forecasting and development of scenarios to ensure territorial development of land use of region. The purpose of the study has been achieved to develop scenarios to ensure territorial development of land use of regions. The tasks of the study are: determining the quantitative basis for the development of scenarios to ensure territorial development of land use at the regional level; Characteristics of typological features of scenarios to ensure territorial development of land use. As a result of the study, the definition of territorial development of land use of regions as a systemic category based on a theoretical and methodological platform, which includes regional and territorial aspects, features of land use, a set of functional, spatial, urban planning, environmental, environmental, investment-innovation, security, social, social, social, social, social, social and social. stakeholder factors whose interaction leads to an increase in the efficiency of land use and the formation of a qualitatively new environment from The use of a monitoring geoinformation system. As a result of the study, it is determined that in most regions in the predicted period there is a development of events under the script 2, where the functional directions of land use are developed and implemented at the low level, spatial, urban planning, environmental, investment-innovative, security, social, social, social plan The trends of growth of the main indicators, there are no possibilities for the use of modern equipment in the field land use. The significant impact of the consequences of Russian aggression and unbalance of regional relationships and asymmetric processes are determined. In order to change the formation of a negative scenario in the forecast period, it is necessary not only to significantly change the tendencies of changes in functional, spatial, urban planning, environmental, investment-innovative, security, social, stakeholder factors, but also actively use modern technologies of geoinformation systems, formation, construction of organizational and spatial mechanism for ensuring the territorial development of land use on regional level. As a result of the systematization of theoretical and methodological approaches, a conceptual apparatus was proposed to determine the territorial development of land use of regions, which is based on a set mathematical tools, modern geoinformation systems tools that allowed to build a quantitative basis for making sound decisions regarding the provision of territorial development of land use at the regional level. The processes of modeling directions of providing territorial development of land use, which are implemented through the use of modern technologies of script approach, developed organizational and spatial mechanism, geoinformation systems, which allowed to propose monitoring procedures to prevent negative phenomena were further developed.